PELATIHAN MEWUJUDKAN GENERASI SEHAT MELALUI ZERO PLASTIC DAN BRAIN GYM - Ardiyanto, Bagas; Rohmat, Alfian Nur; Murrena, Aurelia Evelin; Baskoro, Cahyo; Wibowo, Duwie Kresno; Istiani, Dwi; Wulandari, Fitriana; Sari, Siti Ayu Purnama; Firmansah, Fery; Tasari (WIDHARMA - Jurnal Pengabdian Widya Dharma, 2026)
The purpose of this community service program is to create a healthy generation through Zero Plastic and Brain Gym. This program was held at TPQ Ar-Roudhoh Gunungan, Bareng Lor, North Klaten, Klaten on Tuesday, May 7, 2024. The participants consisted of 28 students and were accompanied by 8 educators. The community service was carried out in three stages, namely the preparation stage, the implementation stage, and the follow-up stage. As a result of the community service, all participants were actively involved in the training activities, and good habits were formed among the students and educators at TPQ Ar-Raudhoh.